2005
DOI: 10.1300/j031v17n01_03
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Caregiver Support Services

Abstract: This study examines the scope and range of existing resources for family caregivers from the perspective of the Area Agencies on Aging (AAAs), which are charged with implementing Title III-E of the reauthorized Older Americans Act. California is used as a case example because of its substantial experience in providing caregiver support services. In particular, we examine the extent and adequacy of resources available in California corresponding to each of the five Title III-E service areas, utilizing data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Our findings is congruent with Guthrie et al (2008) [ 31 ] who reported that relationships, in this case between provider and the family unit inclusive of the patient and family carer, are crucial for establishing good long-term care. Unlike findings from other studies of family carer-provider relationships where providers either avoided or exploited their engagement with family carers [ 18 19 ], family carers and providers in this case mutually sought to work together to support the patient. The organisation understood the important role family carers filled in chronic care management that has largely been invisible in the literature and policies.…”
Section: Discussion/conclusionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our findings is congruent with Guthrie et al (2008) [ 31 ] who reported that relationships, in this case between provider and the family unit inclusive of the patient and family carer, are crucial for establishing good long-term care. Unlike findings from other studies of family carer-provider relationships where providers either avoided or exploited their engagement with family carers [ 18 19 ], family carers and providers in this case mutually sought to work together to support the patient. The organisation understood the important role family carers filled in chronic care management that has largely been invisible in the literature and policies.…”
Section: Discussion/conclusionmentioning
confidence: 72%
“…Kodner and Spreeuwenberg (2002) [ 15 ] suggest successful health and social service integration occurs only if family carers and patients are involved in the planning and implementation of care. However, empirical findings of family carer-provider (usually nurses) relationships highlighted differences between the values and expectations of the two workforces that limited the willingness from both sides to partner in chronic care [ 17 18 19 ]. There is a lack of discussion in the literature on how informal carers – such as unpaid family carers – partner with providers and services to support integrated care.…”
Section: Introductionmentioning
confidence: 99%
“…33 Unfortunately, in many parts of the United States, especially in rural areas, respite services may not be readily available. 34 …”
Section: Before the Move: Making The Decisionmentioning
confidence: 99%
“…Williams (2005) found no differences by race and another research team reported that Hispanic family care-givers used services more than Whites and African-Americans (Kosloski et al 2002), while other researchers cited underuse of resources by minorities, possibly due to low acculturation and other factors (NAC & AARP 2004, Whittier et al 2005). A telephone survey of over 1500 family care-givers showed that ethnicity alone had little influence on service use (Scharlach et al 2008), but that education, emotional support and belief about the meaningfulness of the care-giver role significantly influenced service use.…”
Section: Introductionmentioning
confidence: 97%
“…A telephone survey of over 1500 family care-givers showed that ethnicity alone had little influence on service use (Scharlach et al 2008), but that education, emotional support and belief about the meaningfulness of the care-giver role significantly influenced service use. Whittier and colleagues (2005), studying the use of respite services, also concluded that ethnicity alone did not explain service use. Instead, inadequate marketing of the services, negative attitudes and cost seemed more influential.…”
Section: Introductionmentioning
confidence: 99%